Schlüsselwerke der Vulnerabilitätsforschung. (2019) - Stöhr, Robert; Lohwasser, Diana; Noack Napoles, Juliane; Burghardt, Daniel; Dederich, Markus; Dziabel, Nadine; Krebs, Moritz; Zirfas, Jörg
No abstract available